The Scourge of the Clergy Peter of Dreux, Duke of Brittany - Painter, Sidney (Johns Hopkins University Press, 1937)
Painter's Scourge of the Clergy is a biography of Peter of Dreux, who was the Count of Dreux from 1298 to 1345. This book engages in a conversation with specialists of medieval France and Brittany, given that Peter's career gives historians insight into the quarrels between church and state, the crusades of St. Louis, the struggles between French kings and vassals, and the rivalry of the Capetian and Plantagenet monarchies.